2014
DOI: 10.1037/a0037215
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the social role theory of stereotype content: Observations of groups’ roles shape stereotypes.

Abstract: In applying social role theory to account for the content of a wide range of stereotypes, this research tests the proposition that observations of groups' roles determine stereotype content (Eagly & Wood, 2012). In a novel test of how stereotypes can develop from observations, preliminary research collected participants' beliefs about the occupational roles (e.g., lawyer, teacher, fast food worker, chief executive officer, store clerk, manager) in which members of social groups (e.g., Black women, Hispanics, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
376
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(449 citation statements)
references
References 88 publications
16
376
2
12
Order By: Relevance
“…Working mothers, for example, are perceived as less competent than women without children, whereas women without children are perceived as less warm than working mothers (Cuddy, Fiske, & Glick, 2004;Kervyn, Yzerbyt, Judd, & Nunes, 2009). Not all studies show this trade-off between warmth and competence (e.g., Koenig & Eagly, 2014) which suggests the presence of moderators in determining whether warmth and competence negatively affect each other. However, a substantial number of studies have found evidence for such a trade-off (Kervyn, Yzerbyt, & Judd, 2010), suggesting that ambivalent stereotypes at work pose substantial threats to many groups because being evaluated as high on one dimension can negatively affect evaluations on the other dimension.…”
Section: Stereotype Content Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Working mothers, for example, are perceived as less competent than women without children, whereas women without children are perceived as less warm than working mothers (Cuddy, Fiske, & Glick, 2004;Kervyn, Yzerbyt, Judd, & Nunes, 2009). Not all studies show this trade-off between warmth and competence (e.g., Koenig & Eagly, 2014) which suggests the presence of moderators in determining whether warmth and competence negatively affect each other. However, a substantial number of studies have found evidence for such a trade-off (Kervyn, Yzerbyt, & Judd, 2010), suggesting that ambivalent stereotypes at work pose substantial threats to many groups because being evaluated as high on one dimension can negatively affect evaluations on the other dimension.…”
Section: Stereotype Content Modelmentioning
confidence: 98%
“…Leach, Ellemers, & Barreto, 2007). More recently, Koenig and Eagly (2014) argued and found that competence consists of two separate constructs with distinct effects, namely competence (e.g., intelligence, skill) and agency (e.g., assertiveness, dominance) (see also Carrier, Louvet, Chauvin, & Rohmer, 2014). Although we support critical examinations of the two-dimensional structure of the SCM, these are rather recent developments that have not been subject to extensive scrutiny.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Another perspective on stereotypes is offered by social role theory (Eagly & Steffen, 1984;Koenig & Eagly, 2014). This theory suggests that the distribution of members of different groups into social roles shapes stereotype content.…”
Section: The Mechanics Behind the Male Gamer Stereotypementioning
confidence: 99%
“…For example, women are over-represented in caregiving, communal professions, which results in them being viewed as nurturing and warm. Evidence for this theory exists with respect to a wide range of groups (e.g., Black men and women, gay men, the poor, and senior citizens) and social roles (e.g., secretaries, hair stylists, food service, and store clerks), and the authors explicitly suggest its applicability to leisure and recreational roles as well (Koenig & Eagly, 2014).…”
Section: The Mechanics Behind the Male Gamer Stereotypementioning
confidence: 99%
“…Rasgos como egoístas, fuertes o insensibles aún se asignan con más frecuencia a los hombres, mientras que adjetivos como dulce, emocional o comprensiva se perciben como más típicos de las mujeres (2014). La diferenciación psicológica entre hombres y mujeres, así como la atribución a estas de este tipo de rasgos favorables relacionados con la afectividad y la empatía, se utiliza a veces para legitimar la división de roles dentro del hogar y las diferencias de posición en el mercado de trabajo (Cundiff y Vescio, 2016;Hoffman y Hurst, 1990;Jackman, 1994;Jost y Banaji, 1994;Jost y Kay, 2005;Koening y Eagly, 2014).…”
Section: Estereotipos De Género Y División Del Trabajounclassified